The Prospects of Multilateral vs Regional Liberalization of Trade with Agricultural Products in the Background of New Trends on Food Markets after the 2008 Crisis - Poczta-Wajda, Agnieszka; Sapa, Agnieszka (Studia Oeconomica Posnaniensia, 2017)
This paper aims to identify the role of the WTO in the multilateral liberalization of trade in agri-food products and its alternative - trade regionalism. In the first part of the article we have identified the most important trends characterizing contemporary world agricultural markets after 2008. On the basis of the World Bank NRA estimate, we have also presented the evolution of agricultural policy in countries at different stages of development. The financial crisis and the accompanying food crisis have no permanent influence on the protection of agricultural markets. The attempts to liberalize tariffs in the multilateral and regional dimension are being accompanied by an increase in non-tariff protectionism. This suggests the need to intensify activities towards the liberalization of agricultural trade, both in the WTO as well as within the regional economic groups.